Bridging The Gap in Digital Twin Frameworks: A Comparative Analysis on Building Energy Consumption in The Malaysian Context - Brahim, Juliana; Syazli Fathi, Mohamad; Mohd, Suzila; Dao, Thuy Ninh (International Journal of Sustainable Construction Engineering and Technology, 2025)
Buildings contribute to a substantial portion of global energy consumption, necessitating innovative technologies to enhance energy efficiency. Building Information Modelling (BIM) and Digital Twin (DT) technologies offer promising solutions, with BIM supporting energy-efficient designs and DT enabling real-time energy optimisation. However, DT adoption in Malaysia is limited, particularly in building energy management, due to the absence of tailored frameworks addressing local challenges such as infrastructure readiness, technical expertise, and policy support. Hence, this paper systematically reviews and compares ten existing DT frameworks, focusing on their applicability to building energy management and construction practices. Frameworks were selected based on their emphasis on energy optimisation, integration DT and its relevance to building operations. Content analysis was employed using Atlas.ti to categorise recurring themes, gaps, and limitations across these frameworks. The analysis reveals that existing frameworks often assume a high level of technological maturity and infrastructure readiness, making them less applicable to Malaysia’s developing context. This study highlights these gaps and proposes strategies, including targeted investments, capacity-building, and policy development, to support DT implementation tailored to Malaysia’s needs, advancing energy efficiency in its building sector.